Export Intensity and Plant Characteristics: What Can We Learn from Quantile Regression? - Joachim Wagner (Hamburg Institute of International Economics (HWWA), 2004)
Using quantile regression and a rich cross section data set for German manufacturing plants this paper documents that the impact of plant characteristics on export activities varies along the conditional size distribution of the export/sales ratio.
Keywords: L60; D21; F10; 330; Exports; quantile regression; heterogeneous firms; Verarbeitendes Gewerbe; Export; Regression; Aussenwirtschaft; Mikroökonometrie; Schätzung; Deutschland